Economic Development Planning in Medan City - Salwa Fadhilah Haya; Risfa Dwi Andini; Sultan Rasy Nasyaa; Iyas Alwi Siregar; Sari Wulandari (Penerbit Jurnal Indonesia, 2022)
Economic development in an area must go through several plans and targets both long term and short term. The process leading to the realization of some of these targets is useful for conditioning the capacity for increasing the economy of the community. One of the characteristics of society that has gone hand in hand with economic development is marked by the widespread use of technology and changes in a more positive direction from the mindset of the people to institutional institutions. The research method used as an analytical tool in this study is a descriptive type with the aim of obtaining a projected representation of a participation and procedural regulatory mechanism in the community during the process of preparing the RPJMD in Medan City from 2010 to 2025. The analytical steps used are secondary data or data. supporting information in the form of a collection of information regarding the results of interviews with respondents as well as providing an appropriate presentation with an explanation of the matrix accompanied by the presentation that has been displayed by the researcher. The variety of informants or respondents used as a collection of information in this study involved various elements such as social organizations, elements from the Medan city government to academics under the auspices of universities to the mass media and the main element is the Medan City DPRD. The process of compiling the results of this research is oriented towards a question and answer process or interviews by applying qualitative analysis steps with the aim of criticizing various phenomena in the process of preparing reports and investigating phenomena regarding the research topic. The continuation of the process is a data analysis technique using logical interpretation supported by previously collected data. The results of this study are that in development planning, Medan City has a challenge by having to handle an area of 265.10 km2, with an estimated population density of 9,836.56 people/km2 in 2025. This population increase can be an obstacle in handling development planning., however This is also an opportunity if the government can take advantage of this population increase. For population growth itself in 2025 there will be a decline, which in 2020 is expected to grow by 1.03 to 0.94% in 2025.